Acceptance of TQM and Human Capital in Improving SME Performance - Fitri Lukiastuti; Yanti Pujiastuti (Media Ekonomi dan Manajemen, 2024)
The corporate world is growing more competitive as customers become more savvy. SMEs require a wide range of material and immaterial resources, as well as the capacity to change into more adaptable and lucrative forms to adapt to the shifting demands of the business market, in order to remain competitive. This study aims to examine the correlation between human capitalÂ  and total quality management with entrepreneurial orientation and their impact on performance. Specifically, the study will investigate how market orientation functions as a mediating factor in the link between TQM, HC, EO, and the performance of small and medium-sized enterprises (SMEs) in Semarang. Empirical research has largely neglected to investigate the role of market orientation in mediating the links between TQM, HC, EO, and business performance. This study aims to address the existing knowledge gaps by investigating the direct as well as indirect impacts of TQM, HC, and EO on the performance of SMEs, with MO serving as a mediator. In this study, a questionnaire was employed to gather data from subject matter experts (SMEs) to evaluate the theoretical framework. PLS is utilised in the investigation and testing of hypotheses.